The truth in complexes: why unraveling ion channel multi-protein signaling nexuses is critical for understanding the function of the nervous system - Christophe Altier (Frontiers Research Topics, 2015)
In the search for simple explanations of the natural world, its complicated textures are often filed down to a smoothened surface of our liking. The impetus for this Research Topic was borne out of a need to re-ignite interest in the complex - in this case in the context of ion channels in the nervous system. Ion channels are the large proteins that form regulated pores in the membranes of cells and, in the brain, are essential for the transfer, processing and storage of information. These pores full of twists and turns themselves are not just barren bridges into cells. More and more we are beginning to understand that ion channels are like bustling medieval bridges (packed with apartments and shops) rather than the more sleek modern variety - they are dynamic hubs connected with many structures facilitating associated activities. Our understanding of these networks continues to expand as our investigative tools advance. Together these articles highlight how the complexity of ion channel signaling nexuses is critical to the proper functioning of the nervous system.